On The Hadwiger’s Conjecture - Nemron, Ikorong Anouk Gilbert (Communications in Mathematics and Applications, 2010)
The Hadwiger’s conjecture (see [1] or [2] or [3] or [4] or [5] is well known. In this paper, we show an original Theorem which is equivalent to the Hadwiger’s conjecture.